Association of malnutrition with cognitive frailty in China: a systematic review and meta-analysis - Zhu, Zhiren; Xue, Huiping; Huang, Chunxia; Zhang, Jie; Tu, Jinheng; Ling, Kenan; Gu, Dongmei (Frontiers in Public Health, 2025)
BackgroundWith an aging population, China faces a growing burden of age-related health conditions, including cognitive frailty and malnutrition. This study aimed to investigate the current status of malnutrition in individuals with cognitive frailty in China and to assess the association between the two conditions.MethodsWe conducted a comprehensive search of databases including PubMed, Web of Science, Scopus, Embase, Cochrane Library, CNKI, Wanfang, and Weipu up to April 26, 2024. Meta-analysis was performed using Stata/MP 16, with sensitivity and subgroup analyses to explore heterogeneity, and Begg’s and Egger’s tests to assess publication bias, applying the trim-and-fill method for correction.ResultsOf 2,077 records, 19 were included. The pooled prevalence of cognitive frailty was 26% (95% confidence interval [CI]: 0.17–0.36, p < 0.01), and the prevalence of malnutrition was 45% (95% CI, 0.30–0.58, p < 0.01). A significant association was identified between cognitive frailty and malnutrition (odds ratio [OR] = 4.23, 95% CI: 2.56–6.99, p < 0.001), adjusted to OR = 3.00 (95% CI, 1.87–4.80) post-correction.ConclusionMalnutrition is prevalent among individuals with cognitive frailty in China. Given its higher prevalence in community settings than in hospitals, early screening and specific interventions are crucial to address this issue.